Linux security and hardening : the practical security guide - Cannon, Jason (Packt Publishing, 2018)
"This course will not only teach you the security concepts and guidelines that will keep your Linux servers safe, it will walk you through hardening measures step-by-step. By the end of this course, you will be able to tighten up the security on any Linux system. You'll learn the security weaknesses of the Linux operating system and will be given step-by-step instructions on how to protect those weaknesses. You'll even learn some security concepts that apply to information security as a whole while focusing on Linux-specific issues that require special consideration. What you learn in this course applies to any Linux environment or distribution including Ubuntu, Debian, Linux Mint, RedHat, CentOS, Fedora, OpenSUSE, Slackware, Kali Linux, and more."--Resource description page